Carbazole-based aggregation-induced phosphorescent emission-active gold(I) complexes with various phosphorescent mechanochromisms - Chen, Zhao; Deng, Xiao-Wen; Wang, Xiao-Yan; Wang, An-Qi; Luo, Wen-Tao (Frontiers in Chemistry, 2022)
A series of carbazole-containing gold(I) complexes modified with different substituents were successfully designed and synthesized, and their molecular structures were characterized by nuclear magnetic resonance spectroscopy and mass spectrometry. The aggregation-induced behaviors of these gold(I) complexes were studied by ultraviolet/visible and photoluminescence spectroscopy. Meanwhile, their mechanical force-responsive emissive properties were also investigated via solid-state photoluminescence spectroscopy. Interestingly, all these gold(I)-based luminogenic molecules were capable of exhibiting aggregation-induced phosphorescent emission phenomena. Furthermore, their solids of three gold(I) complexes displayed contrasting mechano-responsive phosphorescence features. More specifically, trifluoromethyl or methoxyl-substituted luminophores 1 and 3 demonstrated mechanochromic behaviors involving blue-shifted phosphorescence changes, and their mechanoluminochromic phenomena were reversible. However, the solid-state phosphorescence of phenyl-substituted luminophor 2 was not sensitive to external mechanical force.